From Little Albert to the Strange Situation; [Do Pequeno Albert À Situação Estranha] - Calquin-Donoso, C (CONICET - Emiliano Aldegani, 2024)
The article problematizes the approach to ethics in psychology research with children in the 20th century and its articulation with ethical codes and principles. Three points of inflection with the literature on the subject are elaborated, namely: (1) a questioning in the production of universals that always put the exclusion of a singular susceptible to be subjected to torture, (2) displacement of the idea that there is a good and a bad reading of prescriptive documents to install an emphasis on the multiplicity of readings and uses that arise from legal, normative, deontological and heuristic frameworks; and (3) an observation of the figure of the researcher enhancing his character marked in a position within socio-historical-material dynamics. Two cases of experimentation with infants in psychology are addressed, corresponding to the case of Little Albert by John B. Watson and Raslie Rayner in 1920, and the experimental protocol of the Strange Situation carried out in the 1970s by Mary Ainsworth and which was the basis of the Attachment Theory invented by John Bowlby. We conclude a series of challenges for training in research ethics in psychology that exceed the margins of an approach centered on the knowledge and management of legal, normative, deontological and heuristic frameworks for the resolution of ethical dilemmas. © 2024 CONICET - Emiliano Aldegani. All rights reserved.